2019
DOI: 10.1039/c9ra03513c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of LaCoO3 perovskite nanoparticle on Daphnia magna: accumulation, distribution and biomarker responses

Abstract: The instability of PNMs in water is of environmental concern. This study shows that in daphnids over 48 h, the mode of action of a representative PNM LaCoO3 is dependent on Co species, which results in the differences in uptake, accumulation, distribution and toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…32 However, concentrations measured in whole organisms do not necessarily mean that contaminant-receptor interactions are occurring, and further information is needed on the site of accumulation and whether the contaminants are undergoing active metabolism and affecting the physiology of the animal. 11 showed the potential of synchrotron XRF imaging for studying biodistribution of Ln in daphnids. This multi-element analysis offers high spatial resolution 2D mapping and is capable of detecting very low metal concentrations within a complete organism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 However, concentrations measured in whole organisms do not necessarily mean that contaminant-receptor interactions are occurring, and further information is needed on the site of accumulation and whether the contaminants are undergoing active metabolism and affecting the physiology of the animal. 11 showed the potential of synchrotron XRF imaging for studying biodistribution of Ln in daphnids. This multi-element analysis offers high spatial resolution 2D mapping and is capable of detecting very low metal concentrations within a complete organism.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al 11 showed the potential of synchrotron XRF imaging for studying biodistribution of Ln in daphnids. This multi-element analysis offers high spatial resolution 2D mapping and is capable of detecting very low metal concentrations within a complete organism.…”
Section: View Article Onlinementioning
confidence: 99%
See 2 more Smart Citations
“…In the past few years, only 12 studies have provided experimental data on the biological impacts of PSC-related chemicals (Table and Figure ). Two fishes (zebrafish and Japanese medaka), , a water flea, ,, a phytoplankton, a chironomus, a nematode, , and bacteria were selected as test species. Three soil plants and soil bacteria , were investigated to evaluate the soil ecotoxicology, and five human cell lines (A549 cell, SH-SY5Y cell, Caco-2/TC7 cell, Beas2B cell, and HepG2 cell) and mouse neurons were assessed via in vitro assay. ,, Even though the aquatic toxicity data accumulated were more than those on soil toxicity and cytotoxicity, the number of reports is still very limited.…”
mentioning
confidence: 99%